2022
DOI: 10.1111/1753-6405.13197
|View full text |Cite
|
Sign up to set email alerts
|

Variations in utilisation of colorectal cancer services in South Australia indicated by MBS/PBS benefits: a benefit incidence analysis

Abstract: Objective: This study investigated variations in healthcare expenditure for colorectal cancer (CRC) patients in South Australia by socioeconomic position (SEP) and remoteness area.Methods: Benefits incidence analysis (BIA) was used to examine healthcare expenditure and utilisation in relation to CRC patients by SEP and remoteness areas. Utilisation data was obtained for patients diagnosed with CRC in 2003-2013 from a dataset linked to a populationbased cancer registry, Medicare Benefits Scheme (MBS), Pharmaceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Although individual and geographical survival rates for CRC vary, this research-based study aimed to look at the various prognostic factors that influence the survival rate of CRC patients in HUSM. This study outcome shows that the overall five-year survival rate in patients with colorectal cancer was 62.5%, which is similar to the data (60%) reported by Barnous, Somi [ 23 ] and 64.5% reported from the Surveillance, Epidemiology and End Results (SEER) Program from 2008 to 2014, as well as in the United States (64.8%) [ 24 ], Australia (63.4%) [ 25 ], including the Asian nations of China (60.1%) [ 26 ], Japan (68.4%) [ 27 ] (68.4%), South Korea (60.0%) [ 28 ], and Iran (58.5%) [ 29 ]. Given the advanced presentation of CRC in the present study among the age groups, the elderly age group (70 years and above) have the poorest survival rate (54.1%) among all the age groups, just as reported in a study in the UK, which revealed that the incidence rates of CRC in the UK are primarily diagnosed in persons aged 75 and above, the highest among 85–89-year-olds, and this groups is associated with the poorest survival prognosis [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…Although individual and geographical survival rates for CRC vary, this research-based study aimed to look at the various prognostic factors that influence the survival rate of CRC patients in HUSM. This study outcome shows that the overall five-year survival rate in patients with colorectal cancer was 62.5%, which is similar to the data (60%) reported by Barnous, Somi [ 23 ] and 64.5% reported from the Surveillance, Epidemiology and End Results (SEER) Program from 2008 to 2014, as well as in the United States (64.8%) [ 24 ], Australia (63.4%) [ 25 ], including the Asian nations of China (60.1%) [ 26 ], Japan (68.4%) [ 27 ] (68.4%), South Korea (60.0%) [ 28 ], and Iran (58.5%) [ 29 ]. Given the advanced presentation of CRC in the present study among the age groups, the elderly age group (70 years and above) have the poorest survival rate (54.1%) among all the age groups, just as reported in a study in the UK, which revealed that the incidence rates of CRC in the UK are primarily diagnosed in persons aged 75 and above, the highest among 85–89-year-olds, and this groups is associated with the poorest survival prognosis [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…The Medicare Benefits Scheme (MBS) and Pharmaceutical Benefits Scheme (PBS) set the fee schedules for private healthcare service subsidies. 16 Services to low-income groups, such as women in our study, receive higher subsidies up to 100%. We conducted a cost-effectiveness analysis, from a health system perspective, to compare the BiOC service with Standard Care in reducing preterm birth.…”
Section: Methodsmentioning
confidence: 62%
“…In SA, previous linked data projects have addressed a range of questions, including concordance with treatment guidelines [40], variation in healthcare expenditure [41], use of colonoscopy pre-colorectal cancer diagnosis [10], and screening-treatment-mortality pathways [42]. A Cancer Data and Aboriginal Disparities (CanDAD) linked dataset was also established, comprising all Aboriginal people living in SA at the time of their cancer diagnosis between 1990 and 2010, and one matched non-Aboriginal person with cancer for each Aboriginal member of the cohort [12].…”
Section: Discussionmentioning
confidence: 99%